PENGARUH CORPORATE GOVERNANCE TERHADAP TRANSPARANSI PADA PERUSAHAAN NON- KEUANGAN DI BEI PERIODE 2012-2016 - Adrian Christianto; Werner Ria Murhadi; Liliana Inggrit Wijaya (CALYPTRA, 2018)
This research aim to analyze affect corporate governance which transparency in measured stock return synchronicity.Research finding indicates that board size (komisaris), institutional ownership andleverage give positiveeffect to transparancy and volatility of firm fundamental give negative effect to transparancy . The another variabels like big4 audit, market to book ratio, and firm size give not effect to transparancy.